The Hugo movie companion : a behind the scenes look at how a beloved book became a major motion picture - Selznick, Brian; Scorsese, Martin; Serlin, David; Buitendijk, Jaap. (New York : Scholastic Press, 2011)
'Brian Selznick takes readers on an intimate tour of the movie-making process as his Caldecott Award-winning book The Invention of Hugo Cabret is turned into a 3-D major motion picture by Academy Award-winning director, Martin Scorsese, written by Academy Award-nominated screenwriter, John Logan.'--Amazon.com.
A brief introduction -- The original book -- The director and his vision -- Assembling the team -- Lights! Camera! Design! -- Filming begins -- The party -- Winding it up.
Includes bibliographical references.
Keywords: Selznick, Brian. -- Adaptations -- Juvenile literature; Selznick, Brian -- Film adaptations -- Juvenile literature; Selznick, Brian. -- Adaptations; Selznick, Brian. -- Film adaptations; Hugo (Motion picture) -- Juvenile literature; Hugo (Motion picture); Motion pictures -- Production and direction -- Juvenile literature; Motion pictures -- Production and direction